Petits tours: representações do circuito turístico em Lawrence Durrel, David Lodge e Didier van Cauwelaert - Isabel Peixoto Correia; Sandra Raquel Silva (Carnets)
The grand tour gave way, progressively, to the small circuits. The great untamed landscapes are almost gone. The great aristocrat paved the way to the tourist. Contact with the indigenous is but a simulation, often rehearsed to confer local flare. The exotic disappeared and adventure seeks refuge in extreme activities – or even in virtual reality. Just like queen Charlotte, to whom contemplating the painting commissioned to Johann Zoffany, The Tribuna of the Uffizi, replaced the in loco visit to the Florentine gallery, the tourists we shall mention, based on three novels by Lawrence Durrell, David Lodge e Didier Van Cauwelaert, limit themselves to the consumption of routes, landscapes and gastronomy of postcard places. Meanwhile, this holyday allows the careful study of the travel companion, thereby allowing the anthropological and sociological analysis to center in the homo turisticus (Lipovetsky), and thus constituting a heterotopy (Foucault).